2021
DOI: 10.3934/jgm.2021011
|View full text |Cite
|
Sign up to set email alerts
|

Matched pair analysis of the Vlasov plasma

Abstract: We present the Hamiltonian (Lie-Poisson) analysis of the Vlasov plasma, and the dynamics of its kinetic moments, from the matched pair decomposition point of view. We express these (Lie-Poisson) systems as couplings of mutually interacting (Lie-Poisson) subdynamics. The mutual interaction is beyond the well-known semi-direct product theory. Accordingly, as the geometric framework of the present discussion, we address the matched pair Lie-Poisson formulation allowing mutual interactions. Moreover, both for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…which is called the momentum-Vlasov equation in the literature [19,25,33]. We remark that this system is precisely equal to conformal kinetic dynamics (2.33) with c being zero.…”
Section: Conformal Kinetic Dynamics In Momentum Formulationmentioning
confidence: 95%
See 1 more Smart Citation
“…which is called the momentum-Vlasov equation in the literature [19,25,33]. We remark that this system is precisely equal to conformal kinetic dynamics (2.33) with c being zero.…”
Section: Conformal Kinetic Dynamics In Momentum Formulationmentioning
confidence: 95%
“…Keeping the same line of thought, further analysis has also been carried out on fluid dynamics [17,18]. Additionally, rich algebraic structure of momentum-Vlasov dynamics is examined in [25], inspired from the moment algebra of Vlasov dynamics, see for instance [28,29,36]. This present work consists of three main sections, in which we propose novel geometries and kinetic theories generalizing the ones in the literature, along with an appendix.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the time evolution generated by (11) terminates at equilibrium states x(e * , n * ) ∈ M ⊂ M (see (18)). The manifold M is the pattern that we have recognized in the phase portrait generated by (11).…”
Section: Equilibrium Thermodynamicsmentioning
confidence: 99%
“…The reduced dynamics is then the compressible fluid motion, whereas M/N has also its own dynamics determined by a Poisson bracket, called Kupershmidt-Manin bracket [42,20]. In a recent study [18,16], it is shown that the relationship between N and M/N can be investigated through the matched-pair geometry, permitting also mutual interactions between N and M/N . This strategy identifies the individual motions of N and M/N as subsystems of M while labeling properly the rest of the terms in the dynamics in M in terms of the mutual actions of N and M/N .…”
Section: Reductions Of Mesoscopic Dynamical Theoriesmentioning
confidence: 99%